Management of modern agricultural community development based on Lanna Thai society - Klianglam, Malinee (MCU Haripunchai Review, 2021)
Lanna Thai society is mainly defined by Chiang Mai, Chiang Rai, Phayao, Lamphun, Lampang, Phrae, Nan, and Mae Hong Son. Most are communities with both old-fashioned agricultural societies. Modern and blended style according to the context of each community with main occupations such as farming, gardening, farming, animal husbandry. and fishing career The occupation of farmers nowadays has changed the traditional way to a new way that often uses chemicals in many production sectors, causing impact to natural resources until it becomes a problem. In addition, the villagers’ values ​​of burning forests cause a lot of smog. problems of shifting cultivation, etc. Therefore, the government should have a policy to promote communities in Lanna to conform to the characteristics of sustainable agriculture. There is a plan to develop new agricultural methods in the long term. and have various projects That allows people to be aware of the impact on their lives that affect the destruction of natural resources to a minimum. And can generate income from production that contributes to the safety and stability of food production of Lanna Thai farmers.